2015
DOI: 10.1159/000369753
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3 Overexpression is Closely Correlated with Poor Prognosis in Human Non-Small Cell Lung Cancer and Mediates its Metastasis Through Upregulating MMP-2 and MMP-9

Abstract: Background/Aims: Golgi phosphoprotein 3 (GOLPH3) is a newly reported oncogene that plays a significant role in regulating cell growth. Recent research has shown that overexpression of GOLPH3 is correlated with patient survival and M classification in breast cancer and other cancers. However, the mechanisms by which GOLPH3 contributes to metastasis in non-small cell lung cancer (NSCLC) have not been previously clarified and are therefore the focus of this work. Methods: Immunohistochemistry (IHC) and western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 26 publications
0
60
0
Order By: Relevance
“…The medium was subjected to SDS-PAGE in an 8% polyacrylamide gel copolymerized with 0.08% gelatin, as previously reported [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The medium was subjected to SDS-PAGE in an 8% polyacrylamide gel copolymerized with 0.08% gelatin, as previously reported [22]. …”
Section: Methodsmentioning
confidence: 99%
“…MMP9 is a member of MMP family, and is secreted by various cancer cells to break down extracellular matrix [23][24][25]. Overexpression of MMP9 has been reported to facilitate metastatic spread of different cancer cells and appears to be an important molecule to directly promote NSCLC metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced expression and upgraded activity of MMP-2 and -9 resulted in degradation of extracellular matrix and destruction of basilar membrane, which facilitated the migration of cancer cells (26,27). On the contrary, restricted expression of MMP-2 and -9 in cancer cells leads to a better prognosis (28)(29)(30). The results from the present study showed that exposure of NSCLC H520 cells to phloretin led to decreased invasion and migratory ability.…”
Section: Discussionmentioning
confidence: 51%